Anomalous Long‐Distance Propagation of ILS LOC Signals by the Es Layer and Its Impact on Aviation Receivers - S. Saito; K. Hosokawa; J. Sakai; I. Tomizawa (Space Weather, 2023)
Abstract Anomalous long‐distance propagation of Very High Frequency radio waves of aeronautical navigation systems was investigated by an airborne Instrument Landing System (ILS) localizer (ILS LOC) receiver installed on the ground at Kure, Japan (34.245°N, 132.528°E). Intense ILS LOC type signals were observed and the received power was strong enough for the aviation receiver to output course deviation. The radio source was identified by receiving the Morse Code for identification as the localizer‐type directional aid (LDA) serving the Runway‐21 of the Hualien Airport, Taiwan (24.0396°N, 121.6221°E) of which beam pointed close to the receiver. This result supports that the source of the signals often observed at the same frequency at the same location is most probably the LDA at the Hualien Airport. The maximum received power was −99 dBm for an omni‐directional antenna. It was strong enough to cause co‐channel interference. Considering stronger power (−70 dBm) found in previous observations at the same frequency at the same location, anomalous propagation of ILS LOC signals by the Es layer could be a cause of interference when a receiver was near the center of the ILS LOC beam. The course deviation output was consistent with the geometry between the beam of Runway‐21 LDA at the Hualien Airport and the receiver. However, the observed course deviation fluctuated remarkably even when the received power was strong enough. The fluctuation of the course deviation may indicate the structure of the Es layer, and observation of the course deviation could be used to diagnose the Es layer structure.